Peran Sosial Budaya Masyarakat dalam Konteks Keagamaan Hindu Kaharingan - Rohana Sari; Enggraeni Enggraeni; I Ketut Suriana; Desembeling Desembeling (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study examines the role of social and cultural structures as mechanisms in reconstructing and maintaining the religious practices of Hindu Kaharingan amidst the challenges of modernization. As a local belief system of the Dayak community in Central Kalimantan, Hindu Kaharingan functions not only spiritually but also as a guardian of cultural identity. This research uses a descriptive qualitative approach with a phenomenological study design. Data was collected through in-depth interviews, participant observation, and document studies to understand the meanings and experiences of the practitioners. The findings reveal that major rituals, such as Tiwah, serve a dual purpose: spiritually, to guide the souls of ancestors, and socially, as a community adhesive that reinforces solidarity through mutual cooperation (handep). Through the lens of Functionalism Theory and Religious Systems Theory, this study reveals that religious ceremonies act as a vital medium for cultural transmission. The active involvement of the younger generation in these rites serves as a non-formal educational mechanism for passing down values, philosophies, and ancestral knowledge within an oral tradition system. Thus, the socio-cultural role of the community functions as an adaptive and resistive strategy that ensures the continuity of the spiritual identity and cultural resilience of Hindu Kaharingan in the contemporary era.